Catena aurea: commentary on the four Gospels, collected out of the works of the Fathers - Thomas, Aquinas, Saint (J.H. and J. Parker, 1864)
v. 1, pt. 1-3. St. Matthew -- v. 2. St. Mark -- v. 3., pt. 1-2. St. Luke -- v. 4, pt. 1-2. St. John.